This entry is an expanded exposition of the rest of the material in Chapter 1.5 of Coxeter's "Introduction to Geometry" where he uses Beecroft's observations to prove the Descartes Circle Theorem.
Given four circles Ei, i = A, B, C, D mutually tangent to each other at six distinct points of tangency, we define the bend , ei, of each circle as plus or minus the reciprocal of the corresponding radius ri, i = A, B, C, D where bend is negative if the circle surrounds the other three and positive otherwise. That is:
This tells us that if we have the radii of three tangent circles we can obtain the fourth using a simple quadratic in the unknown bend.
It is Coxeter's genius to mark the trail of a proof using the most concise and well thought out diagrams and text to make his exposition fully informative to one who is willing to use the guideposts to complete the trail. In this case the proof is not direct. It uses a result of an English "amateur", Philip Beecroft, who rediscovered Descartes work some 200 years later and carried it further. In particular, Beecroft observed that the quartet of circles Ei give rise to another quartet of circles Hi which are also tangent to each other at the same six distinct points and intricately related to the originals. Define Hi for i= A, B, C, D, as the circumcircle of the triangle made up of the three intersections points of its three complementary E-circles, that is, the triplet other than the Eith, and let ni be the bend of Hi. Then Hi is either the incircle or an excircle of the triangle formed by the centers of the complementary circles. In particular:
- Case A: Suppose EB surrounds EC and ED; then HA is the B-excircle of ΔBCD. (Of course case A might have EC or ED) surrounding in which case HA would be the C-excircle or D-excircle of ΔBCD.)
- Case B: Suppose EB, EC and ED are externally tangent; then HA is the incircle of ΔBCD
Consider case A: We learned in the previous two blog entries that eB = -1/s, eC = 1/(s-d), eD = 1/(s-c) and nA = ±(1/rb) where s is the semiperimeter of ΔBCD with sides of length b, c, d and rb is the radius of the B-excircle. (Whether nA is positive or negative depends on the particular configuration of circles we are working with. See note CASEA.)
Now consider case B: Since EB, EC and ED are externally tangent we know that eB = 1/(s-b), eC = 1/(s-c), eD = 1/(s-d). Also we know that nA = ±(1/r) where r = radius of the incircle of ΔBCD. See note CASEB.
Recall from our previous blog entry that r2 = (s-b)(s-c)(s-d)/s and rb 2 = s(s-c)(s-d)/(s-b).
We use the identity: uv + uw + vw = (1/u + 1/v + 1/w)uvw to get eBeC + eBeD + eCeD =
- Case A: (-s + s - d + s - c)(-1/(s)(s-d)(s-c)) = (s - c - d)(-1/(s-b)rb2) = 1 / rb2
- Case B: (s - b + s - c + s - d)(1/(s-b)(s-c)(s-d)) = s (1/r2s) = 1/r2
Since in case A, nA2 = 1 / rb2 and in case B nA2 = 1 / r2, we have in both cases that:
(1)
By symmetry between the E-circles and the H-circles, the relationship holds in the other direction:
(2)
Both hold (again by symmetry in the indices) for all combinations of the subscripts. Thus
(3)
Thus (5)
Note that
CASEA: HA is the B-excircle of ΔBCD.
- Case A.1: Suppose EA is on the far side of line CD from B. Then HB, HC, and HD are surrounded by HA so nA = -1/rb
- Case A.2: Suppose EA is on the same side of line CD as B. Then HB, HC, and HD are externally tangent to HA so nA = 1/rb
CASEB: HA is the incircle of ΔBCD.
- Case B.1: Suppose EA surrounds EB, EC and ED. Then HB, HC, and HD are all externally tangent to HA so nA = 1/rb
- Case B.2: Suppose EA is externally tangent to EB, EC, and ED. Then HA surrounds HB, HC, and HD so nA = -1/rb
An exercise from Coxeter section 1.5
Coxeter refers to the octet of E-circles and associated H-circles as a Beecroft configuration. We now consider Exercise 9. For any four numbers satisfying k + l + m + n = 0, there is a "Beecroft configuration" having bends e1 = k(k + l), e2 = l(k + l), e3 = n2 - kl, e4 = m2 - kl, n1 = l2 - mn, n2 = k2 - mn, n3 = m(m + n), n4 = n(m + n). [Hint: Express e3, e4, n1, n2 as rational functions of e1, e2, n3, n4]
Solution to Exercise 9
We have seen above that equations such as
Note: Suppose (l + k) = 0. Then e1 = e2 = 0 by assignment and (m + n) = 0 because k + l + m + n = 0. Therefore, n3 = n4 = 0. In this case, E1, E2, H3 and H4 are circles with bend 0, i.e., straight lines with E1 parallel to E2 (tangent at infinity) as are H3 and H4. In this case e1 = k(k + l) = 0 = e2 = l(k + l) and n3 = m(m + n) = 0 = n4 = n(m + n). Now k = -l and m = -n mean that e3 = e4 = n1 = e2 = k2 + n2 so circles of radius 1/(k2 + n2) as half the distance between E1, E2 and H3, H4. Using the point at infinity as one of the points of tangency we get a (degenerate) configuration where E3, E4 are tangent to each other as well as E1, E2. H3 contains the intersections of E1E4, E2E4 and E1E2 (infinity), etc. Similarly H1 and H2 can be drawn. Note: if k2 + n2 = 0 then k = l = m = n = 0.
Finally, (as in Coxeter's solution) the parameterization of the problem can be obtained directly from a configuration as follows: Given e1, e2, n3, n4, set e1 = k(l + k), e2 = l(k + l), so e1 + e2 = (k + l)2, (k + l) = ±√[e1 + e2]. Then k = ±e1/√[e1 + e2] and l = ±e2/√[e1 + e2]. Similarly m = ±n3/√[e1 + e2] and n = ±n4/√[e1 + e2] where we used e1 + e2 = n3 + n4. By choosing, say, +, +, -, - we get k + l + m + n = [(e1 + e2) - (n3 + n4)]/√[e1 + e2] = 0.
The following diagram shows a Beecroft configuration with k = 5, l = 4, m = 3, and n = -12 It has values e1 = 45, e2 = 36, e3 = 124, e4 = -11, n1 = 52, n2 = 61, n3 = -27, n4 = 108. E1 has center at the (0,0) and E2 has center on the x-axis. E4 surrounds the other E-circles.